Wage Gaps in Energy Industry: The Role of Sector - Li, Mingming; Tu, Chunlu; Zhang, Fumei (Frontiers in Energy Research, 2022)
Although wage gaps brought about by differences between sectors has been widely discussed, its specificality in the energy industry has received little attention. Due to the nature of the Chinese energy sector as a monopoly and to the influence of the Soviet Union, the wages of public sector employees in the energy industry in China are much less influenced by market mechanisms and are much higher than those in the private sector. This paper is the first article to explore the impact of the public sector on wage gaps in the energy industry using the China Urban Household Survey (UHS) for 2004, 2008, and 2013. The cross-sectional regression results show a significant and continuous wage premium exists between sectors, although the size of the premium declined slightly over time. The Blinder-Oaxaca decomposition finds unexplainable part and discrimination dominates the wage gaps. The quantile regression results show that education and work experience have significant effects on low- and middle-wage groups. The heterogeneity analysis considers two sub-industries and finds that the wage gaps between the two sectors are much higher in the extractive segment of the energy industry than in the production & supply sector of the industry. The results of the study reveal that market-oriented reforms in China are not yet complete, because the obvious premium on wages in the public sector means they are not determined by market mechanisms. Finally, the paper provides policy recommendations from three perspectives: further market-oriented reform, elimination of discrimination, and education & vocational training.